R = {(1,1)(2,2),(3,3),(4,4),(1,2),(2,1),(1,3),(3,1)}

f(x_{1}) = f(x_{2}) ⇒ \(\frac{x_1}{x_1+2}\) =\(\frac{x_2}{x_2 + 2}\)

⇒ x_{1}(x_{2}+ 2) = x_{2} (x_{1} + 2)

⇒ x_{1}x_{2} + 2x_{1} = x_{2}x_{1} + 2x_{2}

⇒2x_{1} = 2x_{2} ⇒ x_{1} = x_{2}

Hence one-one

(iii) a*e = a⇒ \(\frac{ae}{6}\) = a ⇒ e=6

e*a = a⇒ \(\frac{ea}{6}\) = a ⇒ e = 6

identity element = 6

a*b = e ⇒ 9*b = 6 ⇒ \(\frac{9b}{6}\) = 6 ⇒ b = \(\frac{36}{9}\) = 4

b*a = e ⇒ b*9 = 6 ⇒ \(\frac{b9}{6}\) = 6 ⇒ b = \(\frac{36}{9}\) = 4

Inverse element = b = 4